2013
DOI: 10.6000/1929-6002.2013.02.02.7
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Micropropagation of Jatropha curcas L. from Bud Aggregates

Abstract: Entire plants were regenerated from nodes explants of Jatropha curcas L. following a procedure of bud aggregate induction on MS (Murashige and Skoog) medium supplemented with 25 mg.l -1 citric acid, 12.2 mg.l -1 adenine sulfate, 15 mg.l -1 L-arginine, 2.46 M IBA (indole-3-butyric acid), 30 g.l -1 sucrose and 7 g.l -1 of agar, and enriched with different balances of BA (benzyladenine) and L-glutamine. The histological studies performed on aggregates showed that the buds result from both the development of axill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Our results indicate the elevated no. of roots on IBA 2.0 mg/l concentration which are confirmed by previous studies of Datta et al (2007); Mve et al (2013) who observed 19.43% of root formation in Jatropha.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results indicate the elevated no. of roots on IBA 2.0 mg/l concentration which are confirmed by previous studies of Datta et al (2007); Mve et al (2013) who observed 19.43% of root formation in Jatropha.…”
Section: Discussionsupporting
confidence: 88%
“…Maximum shoot size already has been reported by Shrivastava and Banjerjee (2008) who reported that half strength MS media along with IBA (3.0 mg/l) yielded the maximum shoot size. Mve et al (2013) reported maximum root size on 2.46 µM IBA along with 2% sucrose.…”
Section: Discussionmentioning
confidence: 98%